Effect of Work Stress, Extrinsic and Intrinsic Motivation on Job Satisfaction and Employee Performance - Rensi Pradias Sari; Sukmo Hadi Nugroho (Rekayasa, 2023)
Aspects of human resources is one of the important factors that must be considered in the company. In order for companies to survive in the face of increasingly fierce business competition, management needs to make changes within the company with the aim of being able to further improve employee performance so that it is more optimal. The problem that is often faced by every company is regarding employee performance which tends to decline. One of the factors is the work stress experienced by employees. This study aims to explore the effect of job stress and extrinsic and intrinsic motivation on employee performance through the mediation of job satisfaction at the financing company PT BFI Finance Indonesia Tbk. This study uses data collection methods survey and distribution of questionnaires online, respondents were selected by the method purpose sampling. The sample of this research are employees Head Office working in parts Project Management Office, Asset Management and Human Capital at the staff level with a working period of more than 6 months. Data analysis techniques using Structural Equation Modeling (SEM) with LISREL. The results of this study explain that the variables that influence job satisfaction and employee performance are low levels of stress and intrinsic motivation. There are findings where extrinsic motivation has no positive effect on job satisfaction and employee performance.